Poet Rajesh Dhungana's poems evoke a sense of rebellion - Paudel, Laxmi (Adhyayan Journal, 2026)
This article analyzes the rebellious spirit in Rajesh Dhungana’s poetry collection ‘Sukila Mancheko Samahik Mruty’. To date, Dhungana, whose writing has exclusively been poetry, has released two collections: ‘Sukila Mancheko Samahik Mruty’ (2070) and ‘Maile Koko Desh’ (2080). Out of the poet’s two works, only a select few poems from the initial collection, ‘Sukila Mancheko Samahik Mruty’, have been chosen for academic analysis. The primary material for this research article is poet Rajesh’s poetry, while secondary material includes studies on rebellion in poetry. Analysis of collected library resources, primary and secondary, was conducted to uncover the rebellious essence within Dhungana’s poetry. This article examines Rajesh Dhungana as a rebel poet, using subtitles like subject matter, methodology, theoretical concepts, and aspects of rebellion in poetry. Explanation, analysis, and comparison have led to the conclusion that the poet Rajesh embodies an enlightened rebel.